The evolution of 21st century sea-level projections from IPCC AR5 to AR6 and beyond. (12th December 2023) - Slangen, Aimée B.A.; Palmer, Matthew D.; Camargo, Carolina M.L.; Church, John A.; Edwards, Tamsin L.; Hermans, Tim H.J.; Hewitt, Helene T.; Garner, Gregory G.; Gregory, Jonathan M.; Kopp, Robert E.; Santos, Victor Malagon; van de Wal, Roderik S.W.
Abstract: Sea-level science has seen many recent developments in observations and modelling of the different contributions and the total mean sea-level change. In this overview, we discuss (1) the evolution of the Intergovernmental Panel on Climate Change (IPCC) projections, (2) how the projections compare to observations and (3) the outlook for further improving projections. We start by discussing how the model projections of 21st century sea-level change have changed from the IPCC AR5 report (2013) to SROCC (2019) and AR6 (2021), highlighting similarities and differences in the methodologies and comparing the global mean and regional projections. This shows that there is good agreement in the median values, but also highlights some differences. In addition, we discuss how the different reports included high-end projections. We then show how the AR5 projections (from 2007 onwards) compare against the observations and find that they are highly consistent with each other. Finally, we discuss how to further improve sea-level projections using high-resolution ocean modelling and recent vertical land motion estimates.